The Great Mosque of Qalhāt rediscovered. Main results of the 2008-2010 excavations at Qalhāt, Oman - Rougeulle, Axelle; Creissen, Thomas; Bernard, Vincent (Proceedings of the Seminar for Arabian Studies, 2012)
Qalhāt is a vast area of ruins measuring 35 ha, all that is left of a medieval harbour city, which was founded around 1100 and became the twin city of Hormuz and a major port of the Indian Ocean trade in the thirteenth-fifteenth centuries. It was sacked by the Portuguese in 1508 and then finally abandoned in the second half of the sixteenth century. The Great Mosque was the most famous edifice of the city, and was described by Ibn Battūtah in about 1320 and Afonso de Albuquerque in 1508. It was rediscovered on the coast in the middle of the ancient quarter of the city in the course of a preliminary survey during the Qalhāt Project in 2007, and was then excavated in 2008-2010. These excavations show that the mosque was built around 1300 under the rule of Ayāz and Bībī Maryam as stated by Ibn Battūtah, and underwent several periods of restoration or reconstruction before it was ultimately destroyed by the Portuguese. A very impressive building, it was erected on top of a massive basement 5 m high, with under-floor cellars, a cistern, and probable ablution areas. The muṣallā had six bays 3 m wide and five naves 4.10 m wide, a deep mihrab, a minbar, and a minaret. This mosque was highly decorated with stucco and glazed tiles, including lustre and lajvardina tiles from Kashān in Iran. It is a unique piece of architecture, which provides exceptional information about medieval Islamic architecture in Oman.